Effectiveness of Augmented Reality-Integrated Cognitive Conflict-Based Teaching Material in Enhancing Students’ Conceptual Understanding and Attitudes Toward Physics on Light Waves Topic - Holliffa Rohayati; Fatni Mufit; Hidayati Hidayati; Emiliannur Emiliannur (Universitas Negeri Padang, 2026)
Physics learning is expected not only to improve students’ conceptual understanding but also to foster positive attitudes toward physics as an essential component of 21st-century skills. However, the abstract nature of light-wave concepts often leads to misconceptions, low conceptual understanding, and unfavorable attitudes toward physics. To address these issues, cognitive conflict-based teaching materials integrated with Augmented Reality (AR) were developed to facilitate conceptual change and provide more concrete visualizations of abstract phenomena. This study investigated the effectiveness of these teaching materials in improving students’ conceptual understanding and attitudes toward physics on the topic of light waves. A quantitative approach with a quasi-experimental nonequivalent pretest–posttest control group design was employed. The participants were two eleventh-grade classes at SMAN 3 Padang selected through purposive sampling. Data were collected using a four-tier multiple-choice diagnostic test and an attitude questionnaire. The results showed that the percentage of students categorized as understanding concepts increased to 96.00% in the experimental class, while misconceptions decreased to 0.29%. The Mann–Whitney test revealed a significant difference in conceptual understanding, and the Independent Samples t-test indicated a significant difference in students’ attitudes toward physics between the experimental and control groups (p < 0.05). These findings demonstrate that AR-integrated cognitive conflict-based teaching materials effectively enhance both conceptual understanding and attitudes toward physics.